Targeting Cancer-initiating Cells With Oncolytic Viruses - Cripe, Timothy P (Nature Publishing Group, 2009)
Recent studies in a variety of leukemias and solid tumors indicate that there is significant heterogeneity with respect to tumor-forming ability within a given population of tumor cells, suggesting that only a subpopulation of cells is responsible for tumorigenesis. These cells have been commonly referred to as cancer stem cells (CSCs) or cancer-initiating cells (CICs). CICs have been shown to be relatively resistant to conventional anticancer therapies and are thus thought to be responsible for disease relapse. As such, they represent a potentially critical therapeutic target. Oncolytic viruses are in clinical trials for cancer and kill cells through mechanisms different from conventional therapeutics. Because these viruses are not susceptible to the same pathways of drug or radiation resistance, it is important to learn whether CICs are susceptible to oncolytic virus infection. Here we review the available data regarding the ability of several different oncolytic virus types to target CICs for destruction.